“Quando Deus entra, a droga sai":ação da Missão Belém e Cristolândia na recuperação da dependência química na Cracolândia de São Paulo - Trigo, Ana (2016)
This dissertation aims to reveal the ways religion acts in recovering drug addicts. The research is about the work of two religious institutions acting in “cracolândia”, the region of São Paulo town inhabited by crack/drugs users: one is the Missão Belém, of catholic origin; he other is the Cristolândia, of baptist church origin. The word recovering – as well as restauration – is employed, indifferently, by Missão Belém or Cristolândia, indicating that the addict, or dependent, stopped using drugs and is reintegrated, or trying to reintegrated, in normal social life. The study followed seven men and one woman in the final period of the process seeking out to apprehend how they understand religion when they are in “treating houses” of the two institutions. The final conclusion of the research is that religion has a positive paper in recuperating the subjects. But, nevertheless, religion is not the sole element in the process. Familiar life style, ambiance of community life, both created during the recuperation process, seems to function as a support to overcome the problem. In the words of one of the interviewed: “the community cures”